2013
DOI: 10.1016/j.mce.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Differential signaling of the GnRH receptor in pituitary gonadotrope cell lines and prostate cancer cell lines

Abstract: The GnRH receptor (GnRHR) mediates the pituitary functions of GnRH, as well as its anti-proliferative effects in sex hormone-dependent cancer cells. Here we compare the signaling of GnRHR in pituitary gonadotrope cell lines vs. prostate cancer cell lines. We first noticed that the expression level of PKCα, PKCβII and PKCε is much higher in αT3-1 and LβT2 gonadotrope cell lines vs. LNCaP and DU-145 cell lines, while the opposite is seen for PKCδ. Activation of PKCα, PKCβII and PKCε by GnRH is relatively transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 82 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, we found a few genes affected at 6 and 24h, and instead, we identified that the biological processes related to cell adhesion, the cell cycle, and transcription were affected at 24h. GnRHR is known to be a Gi-coupled protein, and it is also possible that cross-talks with the growth factor receptors resulted in protein and lipid changes that altered the growth rate of BPH-1 cells [ 41 , 42 , 54 , 55 ]. Specifically, the gene-grouping analysis showed that, in addition to affecting the G-couple receptor related genes, degarelix-deregulated gene clusters, which included blood vessel development, apoptosis, cell proliferation, inflammation, and EGF-like genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found a few genes affected at 6 and 24h, and instead, we identified that the biological processes related to cell adhesion, the cell cycle, and transcription were affected at 24h. GnRHR is known to be a Gi-coupled protein, and it is also possible that cross-talks with the growth factor receptors resulted in protein and lipid changes that altered the growth rate of BPH-1 cells [ 41 , 42 , 54 , 55 ]. Specifically, the gene-grouping analysis showed that, in addition to affecting the G-couple receptor related genes, degarelix-deregulated gene clusters, which included blood vessel development, apoptosis, cell proliferation, inflammation, and EGF-like genes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, degarelix could deregulate MAPK directly through GnRHR or indirectly through the counteraction of growth factors and hormones present on BPH. Each MAPK cascade is activated by a specific stimulus, although a cross-talk between GnRH and growth factor signaling is also possible [ 41 , 42 , 54 , 55 ]. Complementary, steroidogenic, and cancerous tissues highly express translocator protein (TSPO), and its expression can be controlled by the following pathway component: PKC-MEK-ERK [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The link between the disease and the production of male hormones has been established since 1941 and treatments aimed at blocking the synthesis of these hormones, so called androgen deprivation therapies (ADT), were subsequently developed for clinical use [ 2 ]. A notable example involves usage of gonadotropin releasing hormone (GnRH) agonists and antagonists to reduce serum testosterone levels known as “chemical castration” [ 3 ]. Unfortunately, resistance to ADT occurs within a short period of time and PCa evolves into castration resistant prostate cancer (CRPC), in which the cancer cells produce androgens via de novo and “back door” pathways [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was described that in tumor cells the hGnRHR was exclusively coupled to Gi and consequently inhibit the cAMP accumulation, this action presumably mediates the anti-proliferative effect in these cells (61,67,68). some reports, however, indicated that for tumor cells the hGnRHR is able to activate several G-proteins in a specific cell background (69). The evidence so far indicates that the anti-proliferative response induced by hGnRHR activation results in apoptosis and G2/M arrest in the cell cycle.…”
Section: Human Gnrh Receptor Signaling In Cancer Cellsmentioning
confidence: 99%